Pregnant rats treated with a high-fat/prooxidant Western diet with ANG II and TNF-α are resistant to elevations in blood pressure and renal oxidative stress - Cunningham, Mark W. (Am J Physiol Regul Integr Comp Physiol, 2015)
Oxidative stress and inflammation are risk factors for hypertension in pregnancy. Here, we examined the 24-h mean arterial pressure (MAP) via telemetry and the nitric oxide (NO) and redox systems in the kidney cortex, medulla, and aorta of virgin and pregnant rats treated with a high-fat/prooxidant Western diet (HFD), ANG II, and TNF-α. Female Sprague-Dawley rats were given a normal diet (ND) or a HFD for 8 wk before mating. Day 6 of pregnancy and age-matched virgins were implanted with minipumps infusing saline or ANG II (150 ng·kg(−1)·min(−1)) + TNF-α (75 ng/day) for 14 days. Groups consisted of Virgin + ND + Saline (V+ND) (n = 7), Virgin + HFD +ANG II and TNF-α (V+HFD) (n = 7), Pregnant + ND + Saline (P+ND) (n = 6), and Pregnant + HFD + ANG II and TNF-α (P+HFD) (n = 8). After day 6 of minipump implantation, V+HFD rats displayed an increase in MAP on days 7, 8, and 10–15 vs. V+ND rats. P+HFD rats, after day 6 of minipump implantation, showed an increase in MAP only on day 7 vs. P+ND rats. P+HFD rats had a normal fall in 24-h MAP, hematocrit, plasma protein concentration, and osmolality at late pregnancy. No change in kidney cortex, medulla, or aortic oxidative stress in P+HFD rats. P+HFD rats displayed a decrease in nNOSβ abundance, but no change in kidney cortex NO(x) content vs. P+ND rats. Pregnant rats subjected to a chronic HFD and prooxidant and proinflammatory insults have a blunted increase in 24-h MAP and renal oxidative stress. Our data suggest renal NO bioavailability is not altered in pregnant rats treated with a HFD, ANG II, and TNF-α.